(untitled) (Journal of Science and Technology, 2016)
Brick masonry assemblage composed of brick mass, head joint, and bed joint is subjected to unlade, compressive stress regime. The compressive stress is increased until failure occurs as the bed joint is rotated through O x/2. The results of this test compare favorably with previous finite element simulation. The orthogonal plane of weakness theory, a modified version of a similar phenomenon found in rock mechanics is now applied to masonry assemblages.